2013
DOI: 10.1111/hequ.12015
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Research in Asia: a Publication and Co‐Publication Analysis

Abstract: This study explores higher education research in Asia. Drawing on scientometrics, the mapping of science and social network analysis, this paper examines the publications of 38 specialised journals on higher education over the past three decades. The findings indicate a growing number of higher education research publications but the proportion of Asian publications in relation to the total world publications in higher education research remains stationary. The higher education research community in Asia is he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 31 publications
(76 reference statements)
4
28
1
2
Order By: Relevance
“…The publication/citation approach has been used to identify the most productive and cited authors in higher education research in the USA (Budd and Magnuson 2010), Europe (Tight 2004), and Asia (Jung and Horta 2013), following Tight's (2008) pleas for a greater research effort to map individual contributions to higher education research. Based on publication data, Kosmützky and Krücken (2014) found that international comparative higher education has been in a steady state for the past 20 years.…”
Section: Studies In Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…The publication/citation approach has been used to identify the most productive and cited authors in higher education research in the USA (Budd and Magnuson 2010), Europe (Tight 2004), and Asia (Jung and Horta 2013), following Tight's (2008) pleas for a greater research effort to map individual contributions to higher education research. Based on publication data, Kosmützky and Krücken (2014) found that international comparative higher education has been in a steady state for the past 20 years.…”
Section: Studies In Higher Educationmentioning
confidence: 99%
“…Based on publication data, Kosmützky and Krücken (2014) found that international comparative higher education has been in a steady state for the past 20 years. A further study based on publication data identified East Asian countries as accounting for most of the Asian contribution to the international higher education literature (Jung and Horta 2013). Using citation data, Budd and Magnuson's (2010) citation analysis of USA higher education journals found that citation practices have remained relatively stable over time with regard to the format of items, authors, and sources cited, while Tight's (2014) study revealed limited use of knowledge between USA and European higher education researchers.…”
Section: Studies In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of bibliometric studies of higher education include papers by Silverman (1985) and Budd (1990), (Budd and Magnuson 2010). More recent examples include a study by Horta and Jung (2013), who used community algorithm to analyze general methodological approaches in higher education research in Asia; a study by Jung and Horta (2013), who used a combination of scientometric and social-network analysis methods to compare the state of higher education research in Asia with general patterns in higher education research globally, as well as a study by Tight (2014), which analyzed citation patters in higher education research globally.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2006), but in the context of a developing country such as Pakistan, the situation of the field is bleaker still. For example, out of the 244 universities in Asia engaged in higher education research from 1980 to 2012, 66 percent have published one article and 15 percent published two articles in research journals (Jung and Horta, 2013). Only four universities from Pakistan are engaged in such research publication and are not listed among the top ten countries with the higher percentage of publication, but fall within the institutions with a low level of engagement in higher education research (Ibid).…”
Section: Research At the Universities And Key Definitionsmentioning
confidence: 99%